Micro/nano-structured superhydrophobic surfaces in the biomedical field: part II: applications overview - Lima, Ana Catarina; Mano, João F (Nanomedicine (London, England), 2015)
The properties of surfaces define the acceptance and integration of biomaterials , as well as the material's efficiency when used at research or manufacturing levels. The presence of micro/nano-topographical structures and low surface energies could bring several advantages when highly repellent surfaces are employed in the biomedical field. Biomimetic superhydrophobic surfaces have been explored for diverse applications: as an intrinsic characteristic of biomaterials to be implanted; as materials that exhibit special interactions with biological entities; or to be used in applications. This article aims to focus on the main motivations and requirements in the biomedical field that pushed for the utilization of superhydrophobic surfaces as suitable alternatives, as well as the great evolution of applications that have emerged in the last few years.